Chinese Narratives in Contemporary Indonesian Film - Miaw Lee, Teo (UNIMAS Publisher, 2025)
The year 1998 represents a critical juncture in the historical trajectory of Indonesia, marked by the zenith of anti-Chinese sentiment and discrimination. During this epoch, the nation bore witness to a precipitous surge in violence, resulting not only in the loss of hundreds of lives within the Indonesian Chinese community but also precipitating the demise of the Suharto regime and the dissolution of the New Order regime (1966-1998). The ensuing aftermath of this tumultuous period served as a harbinger for profound socio-political metamorphosis. Subsequent to protracted subjugation under successive regimes, the ethnic Chinese populace experienced a cultural renaissance during the era of 'reformasi.' This resurgence manifested prominently within the cultural milieu, notably in the realm of cinematic expression. Particularly salient was the rejuvenation of ethnic Chinese filmmaking, hitherto subjected to over three decades of cultural erasure and forced assimilation. As regulatory constraints on media relaxed and the pendulum of cultural identity swung back, Chinese-themed films emerged as a substantive manifestation of renewed focus on the narratives of Chinese Indonesians. Filmmakers of note, including Nia Dinata, Riri Riza, and Nan Achnas, imbued their works, such as "Ca-bau-kan" (2002), "Gie" (2005), and "The Photograph" (2007), with the cultural resurgence witnessed during this period. At the core of this cinematic renaissance were the contributions of filmmakers such as Edwin, an avant-garde luminary within the Indonesian cinematic milieu. Commencing his trajectory with short film productions, Edwin transitioned to the creation of feature-length films, including "Blind Pig Who Wants to Fly" (2008) and "Postcards from the Zoo" (2012). Within the crucible of this transformative epoch, Edwin, alongside his contemporaries, played a pivotal role in the dialectical evolution of narrative paradigms. This book seeks to undertake a comprehensive exploration of the nuanced connotations encapsulated within the rubrics of 'Chinese films' and 'Chineseness,' as discernible in contemporary Indonesian cinema. Focusing on the early 2000s, a temporal framework characterized by the cinematic oeuvre of key indigenous filmmakers, this scholarly endeavor aspires to scrutinize the hybridized experiences of the ethnic Chinese minority in Indonesia through the lenses of cinematic narrative, thematic inquiry, and stylistic articulation. Of particular pertinence is the examination of Edwin as a distinctive case study, elucidating an idiosyncratic approach that diverges from the modus operandi of indigenous Indonesian filmmakers. By interweaving personal experiential narratives and embracing an 'accented' stylistic ethos, Edwin adeptly navigates the intricate tapestry of being Chinese in Indonesia. This book contends that, whereas indigenous filmmakers proffer narratives of the Chinese experience from an external vantage point, Edwin, through an introspective lens, captures the nuances of trauma, fragmentation, dislocatedness, and hybridity inherent to the Chinese experience in Indonesia, thereby furnishing a nuanced and authentic portrayal of a community in a state of flux.